Russian Policy in the Orthodox East. Patriarchate of Constantinople (1878-1914) - Gerd, Lora (De Gruyter, 2014)
The book is the first attempt to make a systematic analysis of the Russian ecclesiastical policy in the diocese of the Patriarchate of Constantinople in the period of 1878-1914. It is based mainly on unedited materials from the archives of Moscow, St. Petersburg, Sofia, Athens, Belgrade and Istanbul. Using the existing publications on the political aspects of the Eastern question, the author presents a new understanding of the role of Russia in the East Mediterranean region at the end of the 19th and the beginning of the 20th centuries.